2013
DOI: 10.1002/cctc.201300462
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Characterization, and Photoelectrochemical Properties of Cu‐Doped PbTiO3 and Its Hydrogen Production Activity

Abstract: We report herein the fabrication of visible‐light responsive n‐type PbTiO3 by a combustion method and p‐type Cu‐doped PbTiO3 by an impregnation method to improve hydrogen production activity. Copper was doped into the PbTiO3 lattice up to 1 wt %; any further increase in the loading resulted in the formation of CuO on the surface of the sample. Photoluminescence confirmed that 1 wt % Cu‐doped PbTiO3 effectively suppressed the defects in PbTiO3, which helped to reduce the recombination rate of the photoinduced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…The PL emission intensities of the treated LaFe 0.8 þ LaCu 0.2 samples were weaker than those of the untreated LaFe 0.8 þ LaCu 0.2 , and they gradually decreased as the reduction temperature increased from 250 C to 500 C. This indicates that the presence of metallic Cu species helps to reduce the recombination rate of photo-induced charge carriers. Because the PL emission is the result of the recombination of excited electrons and holes, the lower PL intensity of the samples indicates a lower recombination rate [32]. Table 2 shows the rates of H 2 evolution on LaFe 0.8 þ LaCu 0.2 treated at various temperatures together with the rates on LaFeO 3 and La 2 CuO 4 for comparison.…”
Section: Pl Measurementmentioning
confidence: 99%
“…The PL emission intensities of the treated LaFe 0.8 þ LaCu 0.2 samples were weaker than those of the untreated LaFe 0.8 þ LaCu 0.2 , and they gradually decreased as the reduction temperature increased from 250 C to 500 C. This indicates that the presence of metallic Cu species helps to reduce the recombination rate of photo-induced charge carriers. Because the PL emission is the result of the recombination of excited electrons and holes, the lower PL intensity of the samples indicates a lower recombination rate [32]. Table 2 shows the rates of H 2 evolution on LaFe 0.8 þ LaCu 0.2 treated at various temperatures together with the rates on LaFeO 3 and La 2 CuO 4 for comparison.…”
Section: Pl Measurementmentioning
confidence: 99%
“…The other two fitted peaks Ti 2p 2 and Ti 2p 4 are located at 458.7 and 464.1 eV, respectively, which indicating the Ti 4+ in TiO 2 . Compared with the related binding energy of Ti 2p(3/2) reported in the literature, Ti 2p(3/2) in TiO 2 shows a slight negative shift, indicating the electrons are transferred from PbTiO 3 to TiO 2 . The presence of Pb(VI) and electrons transferred from PbTiO 3 to TiO 2 confirm that a heterojunction is formed at the interface between TiO 2 and PbTiO 3 .…”
Section: Resultsmentioning
confidence: 65%
“…In the XPS spectrum of Ti 2p (Figure C), the two fitted peaks Ti 2p 1 and Ti 2p 3 for Ti 2p(3/2) and Ti 2p(1/2) are located at 458.0 and 464.0 eV, respectively, indicating the Ti 4+ in PbTiO 3 . The other two fitted peaks Ti 2p 2 and Ti 2p 4 are located at 458.7 and 464.1 eV, respectively, which indicating the Ti 4+ in TiO 2 . Compared with the related binding energy of Ti 2p(3/2) reported in the literature, Ti 2p(3/2) in TiO 2 shows a slight negative shift, indicating the electrons are transferred from PbTiO 3 to TiO 2 .…”
Section: Resultsmentioning
confidence: 96%
“…Strong and sharp diffraction peaks indicate that the as‐synthesized sample is well crystallized. Apart from this, the impurity peak was not seen, which confirmed that the as‐synthesized sample successfully prepared single phase with high purity ,. By applying the Scherrer formula for the high‐intensity peak (101) plane, the crystallite size of PbTiO 3 was determined via X‐ray diffraction data by applying the following relation…”
Section: Resultsmentioning
confidence: 67%
“…Further the most important peak in O(1 s) region (see fig. 3(d)) at 527.1 eV i. e. most intense peak at smaller binding energy is attributed to lattice oxygen (Ti−O band), whereas the minor peak at 529.5 eV (higher binding energy) is assigned to surface oxygen, that is very usual in sample with high surface energy ,,,…”
Section: Resultsmentioning
confidence: 99%